Discursive and methodological aspects of the study of the Kazakh Khanate in Turkish historiography - Azmukhanova, Aiman; Egamberdiyev, Mirzahan (Turkic Studies Journal, 2025)
This article examines the discursive and methodological aspects of studying the Kazakh Khanate in Turkish historiography. In recent decades, Turkish scholars have shown increasing interest in Central Asian history. This is due to several factors: first, political and cultural ties between Kazakhstan and Turkey have fostered academic exchanges; second, within Turkology and Eurasian studies in Turkey, there has been a growing focus on Kazakh history as part of the broader history of Turkic peoples; third, there-evaluation of Ottoman and post-Ottoman historiographical traditions has influenced approaches to regional history, including the Kazakh Khanate. However, despite the significant number of studies, Turkish historiography still faces debates on methodology, source interpretation, and historiographical concepts. The study aims to analyze the discourses and methodological approaches of Turkish historians regarding the Kazakh Khanate and the patterns of its statehood formation. The key objectives include identifying trends in Turkish historiography, assessing the influence of methodological traditions, analyzing source materials, and examining the impact of ideological, political, and academic factors. The research’s novelty lies in its comprehensive analysis of historiographical materials and methodological foundations of Kazakh Khanate studies in Turkey. Compared to previous works, this article provides a systematic examination of conceptual and methodological tools, highlighting key trends and developments in historiography. The comparative-historical method in future research allows us to contrast Turkish historiographical perspectives with those from Kazakhstan, Russia, and Western academia. Discourse analysis helps identify narrative features, rhetoric, and key concepts employed by Turkish historians. Content analysis of texts reveals dominant themes, prevailing interpretations, and shifts in scholarly perspectives. A critical-analytical method is also applied to explore methodological challenges and historiographical disputes. The findings provide insights into the current state of Kazakh Khanate studies in Turkish historiography, highlighting key methodological issues. The identified patterns contribute to understanding the influence of political and ideological factors on historiographical discourse, as well as the extent to which Turkish scholars incorporate various theoretical-methodological approaches. The conclusions may be valuable for further research in Turkology and the study of historiographical interactions between Kazakhstan and Turkey.